The influence of subseismic-scale fracture interconnectivity on fluid flow in fracture corridors of the Brejões carbonate karst system, Brazil. (July 2022) - Furtado, Carla P.Q.; Medeiros, Walter E.; Borges, Sergio V.; Lopes, Juliana A.G.; Bezerra, Francisco H.R.; Lima-Filho, Francisco P.; Maia, Rubson P.; Bertotti, Giovanni; Auler, Augusto S.; Teixeira, Washington L.E.
Abstract: The present study used a multitool approach to characterize fractures of several orders of magnitude in large fracture corridors, caves, and canyons to investigate their impact on fluid flow in carbonate units. The study area is the Brejões carbonate karst system that is located in the Neoproterozoic Salitre Formation in the Irecê Basin, São Francisco Craton, Brazil. The approach included satellite imagery, used for interpreting the regional structural context, Unmanned Aerial Vehicle (UAV) and ground-based Light Detection And Ranging (LiDAR) imagery, used for detailed structural interpretation. Regional interpretation revealed that fracture corridors, caves and canyons occur along a N–S-oriented anticline hinge. An advanced stage of karstification caused fracture enlargement and intrabed dissolution, and the formation of caves and canyons. A river captured by the highly fractured zone along the anticline hinge played an important role as an erosive agent. Detailed characterization of fracture corridors comprised structural analysis, topological studies, persistence estimations, power-law fitting of fracture trace length distributions, and identification of network backbones. Our results indicate that fracture corridors comprise four subvertical fracture sets: N–S and E-W and a conjugate pair, NNE-SSW and NW-SE. Fractures observed in the caves show the same dominant directions. Fracture directions are consistent with a common origin associated with the anticline folding. Fracture traces range from 1.0 m to 300 m, comprising both subseismic (<50 m) and seismic scale fractures (>50 m). Networks have dominance of node terminations Y and X (notably Y), CB values higher than 1.8, high P20 and P21 persistence values, and highly interconnected backbones. Fracture network connectivity is associated with power-law exponents greater than 2.5 for the fracture trace distributions, indicating large influence of subseismic-scale fractures on fluid flow. As the final result of folding and karstification, large volumes of secondary macroporosity were created, particularly in the zone of maximum fracture intensity around the hinge zone of the anticline. This scenario can be used to understand better oil reservoirs formed in similar structural controls in near-surface conditions. Highlights: The Brejões carbonate karst system (Irecê Basin, Brazil) is studied using satellite, UAV, and LiDAR images Satellite images allow to identify that fracture corridors, caves, and canyons occur along the hinge of a regional anticline. UAV and LiDAR images allow detailed characterization of fracture networks in fracture corridors and caves, respectively. Fracture studies comprise structural, topological, persistence, trace length, and backbone characterization. Results evidence large influence of subseismic-scale fractures on the network interconnectivity and fluid flow.